Analysis of Patient Satisfaction Levels with Pharmaceutical Services at Rumbai Community Health Center, Pekanbaru City in 2024 - Al Fadhilah, Shafira; aryani, Fina; wenila, Septia; rambe, Septy amelia rizki; arsila, Sherly putri; anissa, Siti nurul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Pharmaceutical services are a form of pharmaceutical care which aims to maintain the quality of pharmaceutical preparations and support the success of the therapy the patient undergoes during treatment. Pharmaceutical services are one part of the health services at the Community Health Center. Puskesmas is a technical implementation unit of the District/City Health Service which is responsible for carrying out health development in a work area (Permenkes, 2020). The aim of this research is to determine the level of patient satisfaction with pharmaceutical services at the Rumbai Community Health Center. The method used is descriptive research (Non-Experimental) with a quantitative approach. The research instrument is a questionnaire sheet. The sampling method is purposive sampling. The number of samples in this research was 100 people. Data collection uses a Likert scale. The level of patient satisfaction is measured against five (5) dimensions of service quality, namely the dimensions of Responsiveness, Reliability, Assurance, Empathy, Tangibles. The results of this research show that the level of patient satisfaction with pharmaceutical services at the Puskessmas Rumbai shows that patient satisfaction is in the Responsiveness dimension (71.75%), Reliability (72.66%), Assurance (74.3%), Empathy (75%) , and Physical Evidence (Tangible) (67.3%). So the average percentage level of patient satisfaction at the Rumbai Health Center overall from 5 dimensions is 72.2% with the satisfaction classification being satisfied.